PROLIFERATION DES MUTUELLES FINANCIERES INFORMELLES DANS LA VILLE D’ISIRO - Damas ESOLE KESOLE KAYA; Chico BOLO NDENDELE; Bibiche-Modestine LAUNA MONDIYO (IJRDO - Journal of Business Management, 2020)
This study focuses on the proliferation of informal financial mutuals in the City of Isiro. The choice to undertake this study aims to identify the causes of the plethora of these informal financial mutuals and to measure the level of correlation between the need for funding and the influx of financial mutuals in the city of Isiro. The results of the investigations reveal that there is a positive linear correlation between the financing needs of the members of these financial structures and the influx of informal financial mutuals in the City of Isiro. The presumption is that the search for capital by the economic agents or need in financing in a precarious economic situation of the formal financial structures explains to 99,98% the massive presence of the informal financial mutuals in the City of Isiro and, the 0,02 % represent the other factors or causes of this influx (the spirit of savings and credit to guard against the vagaries of life as well as the assurance of economic growth, the spirit of mutual aid, the spirit community, the cooperative environment).